2006
DOI: 10.1080/10934520500423592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Platinum Group Metals on the Environment: A Toxicological, Genotoxic and Analytical Chemistry Study

Abstract: Recent studies show particles of Platinum Group Metals (PGMs); primarily platinum, palladium and rhodium; released from automobile catalytic converters are being deposited alongside roadways. This deposition is leading to increasing concentrations of PGMs in the environment, raising concerns about the environmental impact and toxicity of these elements in living organisms. The objective of this study was to determine how PGMs alter the patterns of growth, development, and physiology by studying the toxicologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…A possible explanation for this finding is that ongoing exposure to low-level platinum in neural tissue, as well as any residual systemic effects, may limit resolution of the acute and dose-dependent sensory neuropathy, hypothetically also contributing to ongoing damage. 54 The biokinetic behavior of platinum closely resembles that of other toxic metals (eg, mercury and chromium 55,56 ) in which serum and urine concentrations also correlate with toxic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this finding is that ongoing exposure to low-level platinum in neural tissue, as well as any residual systemic effects, may limit resolution of the acute and dose-dependent sensory neuropathy, hypothetically also contributing to ongoing damage. 54 The biokinetic behavior of platinum closely resembles that of other toxic metals (eg, mercury and chromium 55,56 ) in which serum and urine concentrations also correlate with toxic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3), increasing PGE concentrations have been noted in ice cores (1,4) and snow (5)(6)(7) in remote regions. In general, all PGEs are immobile (8) except Os, which can form volatile OsO 4 during high-temperature industrial processes such as smelting of concentrated ores (9). Anthropogenic Os has been observed in estuaries (10,11), coastal sediments (12,13), and lakes (3).…”
mentioning
confidence: 99%
“…A recent study (Gagnon et al 2006),has shown that particles containing Pt, Pd, and Rh are being released in the road side, leading to an increased deposition of these metals in the environment, and to toxicity, affecting unfavorably the living organisms.…”
Section: Introductionmentioning
confidence: 99%